Automation and financial efficiency: A case study of Procredit Savings and Loans Company Limited - Asante, Enoch Obeng (2014)
A thesis submitted to the Department of Accounting and Finance, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirement for the award of Master of Business Administration (Banking and Finance)